Experimental study of urinary stones - Yu. G. Alyayev; Yu. A. Efimova; G. M. Kuz’micheva; I. Yu. Lovchinovskiy; A. S. Olshanskaya; E. V. Filosofova; L. M. Rapoport; V. I. Rudenko (Тонкие химические технологии, 2006)
Study of urinary stones of surgical removal has been fulfiled by complex methods. Information of phase and element composition have been received, microstructural examination has been made, causes of anomalous hardness of some stones have been found.